Prognostic Value of Pretreatment Metabolic PET Parameters in Cervical Cancer Patients With Metabolic Complete Response After Concurrent Chemoradiotherapy. (September 2018) - Son, Seung Hyun; Jeong, Shin Young; Chong, Gun Oh; Lee, Yoon Hee; Park, Shin-Hyung; Lee, Chang-Hee; Hong, Chae Moon; Jeong, Ju Hye; Lee, Sang-Woo; Ahn, Byeong-Cheol; Lee, Jaetae
Abstract : Purpose: Cervical cancer may recur after concurrent chemoradiotherapy (CCRT), even in patients with metabolic complete response (mCR) on post-CCRT 18 F-FDG PET. We retrospectively analyzed the value of metabolic parameters, measured by pretreatment PET, as prognostic factors for predicting recurrence and death in cervical cancer patients with mCR. Methods: In 61 patients who reached mCR on post-CCRT, metabolic PET parameters including SUVmax, metabolic tumor volume (MTV), and total lesion glycolysis (TLG) of the primary tumors, as well as those of the metastatic lymph nodes, were measured by pre-CCRT PET. Total MTV and total TLG were also measured from primary tumors and metastatic lymph nodes. Survival analyses for disease-free survival (DFS) and overall survival (OS) were performed. Results: Eleven patients (18.0%) presented with recurrence of cervical cancer, and 12 (19.7%) died during follow-up. SUVmax, MTV, TLG of metastatic lymph nodes, and total TLG could significantly predict DFS, and nodal SUVmax could predict OS. Para-aortic lymph node metastasis also significantly correlated with both DFS and OS. In multivariate analysis, nodal SUVmax and para-aortic lymph nodes metastasis were prognostic factors for DFS, and the best predictor was nodal SUVmax. For OS, nodal MTV and para-aortic lymph node metastasis were significant prognostic factors in multivariate analysis, and the best predictor was para-aortic lymph node metastasis. Conclusions: Metabolic PET parameters, SUVmax or MTV values of metastatic lymph nodes, may be surrogate prognostic markers for recurrence or death in patients with locally advanced cervical cancer who reached mCR after definitive CCRT.